Analysis of the correlation between heart rate variability and palpitation symptoms in female patients with long COVID - Jiang, Yu; Cheng, Yan; Xiao, Jingwen; Wang, Yicheng; Chen, Geng; Zhang, Yan (Frontiers in Cardiovascular Medicine, 2023)
Objectives To analyze the correlation between heart rate variability (HRV) and palpitation symptoms in female patients with long COVID. Methods A total of 272 female healthcare workers who were infected with SARS-CoV-2 for the first time in December 2022 at Fuzhou First Hospital affiliated with Fujian Medical University, were selected as study subjects. These subjects were divided into three groups based on their symptoms: a group with palpitations (70 cases), a group without palpitations but with other symptoms (124 cases), and a group consisting of asymptomatic cases (78 cases). The study compared the general information, COMPASS-31 scores, quality of life scores, and HRV parameters among the three groups. Furthermore, it analyzed the factors influencing palpitation symptoms in female patients with long COVID. Results Compared to the other two groups, the HRV parameters SDNN, HRVIndex, LF, and TP were significantly reduced in the group with palpitations (p < 0.05). Multivariate analysis revealed that HRVIndex (p = 0.016; OR: 0.966, 95% CI: 0.940∼0.994) had a significant impact on palpitation symptoms in female patients with long COVID. Conclusions The symptoms of palpitations in female patients with long COVID were found to be related to HRV parameters. Autonomic dysfunction may be connected to the occurrence of palpitation symptoms in long COVID.